Hazardous Waste Management - Nik Norulaini Nik Ab. Rahman (Universiti Sains Malaysia, 2009)
Chapter 1: Introduction -- Chapter 2: Classification and Characterization of Hazardous Wastes -- Chapter 3: Storage of Hazardous Wastes -- Chapter 4: Handling, Transportation and Disposal of Hazardous Wastes -- Chapter 5: Emergency Planning and Response -- Chapter 6: Malaysian Envitronmental Legislations